Draft Annual Plan 1995-96 Volume-II Government of Karnataka - Planning Commission (Planning Commission, 1995)
Crop Husbandry Soli and Water Conservation Animal Husbandry Food Storage and Warehousing Agricultural Research and Education Agricultural Financial Institutions Special Programme for Rural Development, Hyderabad Karnataka. Dev. Programme State Border Area Devt. Programme, Transmission and Distribution Non-Conventional Sources of Energy Industry and Minerals Mining, Non-Ferrous Mining Ports and Light Houses Civil Aviation.
Government of Karnataka
Planning, Institutional Finance and Statistics and Science and Technology Department
Keywords: Progress of Expenditure; Abstract of Annual Plan 1994-95; Proposed Outlay for the Annual Plan 1995-96; Physical Targets and Achievements during the Annual Plan; Proposal for Spill over and On-going to Programmes/Projects; Proposals for maximizing benefits of completed Projects; Summary Statement Proposals for Programmes/ Projects; Centrally Sponsored Schemes; Minimum Needs Programme Outlay/ Expenditure